2018
DOI: 10.1002/hed.25318
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of nerve fibers around the carotid bifurcation with use of a 9.4 Tesla microscopic magnetic resonance diffusion tensor imaging with tractography

Abstract: BackgroundPrecise imaging of nerves have been challenging in the head and neck region, mainly due to low spatial resolution. Here, we investigated how nerves in the head and neck region could be visualized using an ultra‐high magnetic field MR system.MethodsWe used formol‐carbol‐fixed human cadaveric necks and obtained MR diffusion tensor images (DTIs) using a 9.4 Tesla (T) ultra‐high magnetic field MR system. Afterward, we prepared tissue sections and checked the anatomic relationships between the neurons and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…We segmented and quantified the morphology of the largest fiber bundle in the sheath, consistent with prior studies; the largest cervical fascicle can be clearly identified as the VN both in vivo and in the micrographs, and it is the target of cuff electrodes for electrophysiology experiments. The identities of the smaller bundles in the carotid sheath are unclear; possibilities include smaller cervical vagal fascicles, vagal branches [e.g., superior laryngeal branch ( Licursi de Alcântara et al, 2008 )], sympathetic chain ( Ding et al, 2011 ), hypoglossal nerve, glossopharyngeal nerve, spinal accessory nerve ( Saito et al, 2018 ), and ansa cervicalis ( Usami et al, 2013 ). The sizes of our rat cervical nerves were comparable to literature ( Fazan and Lachat, 1997 ; Licursi de Alcântara et al, 2008 ), whereas our rat subdiaphragmatic nerves trended larger ( Prechtl and Powley, 1985 ; Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…We segmented and quantified the morphology of the largest fiber bundle in the sheath, consistent with prior studies; the largest cervical fascicle can be clearly identified as the VN both in vivo and in the micrographs, and it is the target of cuff electrodes for electrophysiology experiments. The identities of the smaller bundles in the carotid sheath are unclear; possibilities include smaller cervical vagal fascicles, vagal branches [e.g., superior laryngeal branch ( Licursi de Alcântara et al, 2008 )], sympathetic chain ( Ding et al, 2011 ), hypoglossal nerve, glossopharyngeal nerve, spinal accessory nerve ( Saito et al, 2018 ), and ansa cervicalis ( Usami et al, 2013 ). The sizes of our rat cervical nerves were comparable to literature ( Fazan and Lachat, 1997 ; Licursi de Alcântara et al, 2008 ), whereas our rat subdiaphragmatic nerves trended larger ( Prechtl and Powley, 1985 ; Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies described the successful application of DTI and DTT in extraforaminal cranial nerve imaging. 12,67–70 But, most reports only describe DTT of the proximal nerve branches with varying reference values. 68,71 DTT of the small distal cranial nerve branches remains challenging and, for the time being, is mostly of scientific value.…”
Section: Introductionmentioning
confidence: 99%